Soybean (Glycine max) Nodule Physical Traits Associated with Permeability Responses to Oxygen. - Purcell, L. C. (1993)
Nodule permeability (P) controls the amount of O2 entering the nodule and is an important determinant of N2 fixation. Modulation of water volume in the intercellular spaces of the nodule cortex was hypothesized to change the effective thickness of a diffusion barrier and account for changes in P. This hypothesis was examined by evaluating physical traits of nodules that may affect P. The first test of the hypothesis was to determine whether alterations in P may result in changing both the density and the air space content of nodules as the water content of intercellular spaces was varied. Density of nodules exposed to 21 kPa O2 increased as the time following detachment from the plant increased from 5 to 60 min. Nodules from soybean (Glycine max [L.] Merr.) plants shaded for 48 h had a lower fractional air space content than nodules from control plants. Nodule detachment and prolonged shading decreased P, and the increase in density and decrease in fractional air space content associated with decreased P in these treatments supports the proposed hypothesis. The second test of the hypothesis was to determine whether nodules released water easily in response to water potential gradients. The intrinsic capacitance of nodules determined by pressure-volume analysis was 0.29 MPa-1 and indicated that the tissue can release relatively large amounts of water from the symplast with only small changes in total nodule water potential. Estimates of the bulk modulus of elasticity ranged from 0.91 to 2.60 MPa and indicated a high degree of elasticity. It was concluded that the physical properties of nodules were consistent with P modulation by the release and uptake of intercellular water in the nodule cortex.